Management of radioactive waste the issues for local authorities : proceedings of the conference organized by the National Steering Committee, Nuclear Free Local Authorities, and held in Manchester on 12 february 1991 - Kemp, Stewart (Thomas Telford, 1991)
Radioactive waste poses one of the most divisive environmental problems of the 1990s. This book explores key issues facing local government, including the implications of current proposals to develop a deep disposal facility for low level and intermediate level radioactive waste.